Self-Reported Depressive Symptoms Might be Associated with Sudomotor Dysfunction in Chinese T2DM Patients - Ji, Lijin; Zhang, Yuanpin; Zhang, Qi; Zheng, Hangping; Sun, Wanwan; Zhu, Xiaoming; Zhang, Shuo; Lu, Bin; Su, Liang; Shi, Hongli; Li, Yiming; Liu, Xiaoxia (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aims To determine the relationships of sudomotor functions, nerve conductions and self-reported depressive symptoms in Chinese type 2 diabetes (T2DM) patients.Methods T2DM patients in a single community health center were included in this study. Demographic, medical and laboratory data were collected. Michigan Neuropathy Screening Instrument (MNSI) examination was conducted in all patients. SUDOSCAN test and Point-of-care Nerve Conduction Device (DPN-check) were conducted and all the patients finished the Patient Health Questionnaire-9 (PHQ-9).Results A total of 162 T2DM patients (74 males and 88 females) were included. The mean age was 69.0±7.2 years and the mean course of diabetes was 10.5±8.0 years with a mean HbA1c level of 7.3±1.4%. Thirty of them (18.5%) had self-reported depressive symptoms (PHQ-9 scores≥5). Diabetic peripheral neuropathy (DPN) was diagnosed according to the MSNI examination in 74 patients. Electrochemical skin conductance (ESC) values of both hands and feet were significantly lower in patients with depressive symptoms (Hands ESC: 60.63±18.92 vs. 67.64±16.02 μS, p<0.05; Feet ESC: 59.60 ± 15.19 vs. 66.19±14.99 μS, p<0.05). The proportion of patients with moderate to severe depressive symptoms were significantly higher in those with ESC values<60 μS (13.33% vs. 3.846%, p<0.05). Hands ESC values were negatively related to PHQ-9 scores (r =− 0.168, p<0.05). After adjusting for variables, hands and feet ESC values remained negatively related with depressive symptoms (β =− 0.036 and−0.038, p<0.05). Female were positively related to depressive symptoms with odds ratio 3.4 (95%CI 1.1–10.5, p<0.05).Conclusion Self-reported depressive symptoms might be associated with sudomotor dysfunction in Chinese T2DM patients.
Keywords: T2DM; depressive symptoms; diabetic neuropathy; SUDOSCAN; DPN-check